Eksistensi Generasi Millenial dalam Berwirausaha di Era Digital (Studi Kasus Online Shop Denia Donuts Palembang) - Depi Kurniati (Journal Science Innovation and Technology (SINTECH), 2021)
The development of technology and access of information that is not limited to changing the perspective also provides opportunities for millennial generations to be able to develop various technology-based businesses. So they are demanded to be able to seize these opportunities. This study aims to determined the used of Social Media by Millennials and the challenges of Business in the Social Media Era. This research was a qualitative research with case study method. Data collection techniques used observation and interviews. As for data analysis, namely qualitative data analysis used the Miles and Hubbermen models which consist of three steps, namely data reduction, data presentation, drawing conclusions or verification. The results of this study indicated the use of social media by Denia Donuts is relatively large. In the aspect of utilizing social media as a means of interaction with consumers comes first with a percentage of 24.8% and the smallest indicator is the use of social media to find out about the quality of similar products with a percentage of 10.5%. As for several factors that determine the high success of the use of social media by Denia Donuts as a means of influencers, online motorcycle taxi users, and channels such as Facebook, Instagram and WhatsApp. While business challenges in the era of social media are changing consumer desires, high competition and consumer testimonials